Creating the national security state : a history of the law that transformed America - Stuart, Douglas T. (Princeton University Press, 2008)
For the last sixty years, American foreign and defense policymaking has been dominated by a network of institutions created by one piece of legislation--the 1947 National Security Act. This is the definitive study of the intense political and bureaucratic struggles that surrounded the passage and initial implementation of the law. Focusing on the critical years from 1937 to 1960, Douglas Stuart shows how disputes over the lessons of Pearl Harbor and World War II informed the debates that culminated in the legislation, and how the new national security agencies were subsequently transformed by.